Answer: (3, 1 ) Step-by-step explanation: Given the 2 equations y = – x + 4 → (1) y = x – 2 → (2) Substitute y = x – 2 into (1) x – 2 = – x + 4 ( add x to both sides ) 2x – 2 = 4 ( add 2 to both sides ) 2x = 6 ( divide both sides by 2 ) x = 3 Substitute x = 3 into either of the 2 equations and solve for y Substituting into (2) y = 3 – 2 = 1 solution is (3, 1 ) Log in to Reply

Answer:(3, 1 )

Step-by-step explanation:Given the 2 equations

y = – x + 4 → (1)

y = x – 2 → (2)

Substitute y = x – 2 into (1)

x – 2 = – x + 4 ( add x to both sides )

2x – 2 = 4 ( add 2 to both sides )

2x = 6 ( divide both sides by 2 )

x = 3

Substitute x = 3 into either of the 2 equations and solve for y

Substituting into (2)

y = 3 – 2 = 1

solution is (3, 1 )